ENVIRONMENTAL SUSTAINABILITY APPRAISAL OF THE ATRIAL FIBRILLATION CARE PATHWAY - Munawar, Sana (2016)
An appraisal of the Atrial Fibrillation care pathway regarding its environmental impact using environmental metrics of CO2 emissions, water use and waste production.